The relationship between the Orange Free State and the Rolong of Thaba 'Nchu during the presidency of J.H. Brand, 1864-1888 - Wales, Janet Mary (Rhodes University, Faculty of Humanities, Department of History, 1980)
During the period 1864 to 1888, President J .H. Brand of the Orange Free State Republic had to deal with two Rolong chiefs at Thaba 'Nchu. The first, Chief Moroka II, ruled the Seleka tribe from 1829 to 1880, while his successor Tsipinare, a Tshidi-Rolong, ruled from 1880 to 1884. The majority of the Rolong at Thaba 'Nchu were of the Seleka division, but the minority groups, the Tshidi and Rapulana, also played an important role in the tribe's relations with the Free State.
Keywords: Rolong (African people) -- Politics and government; Rolong (African people) -- Government relations; Free State (South Africa) -- Native races